Basalt–trachybasalt samples in Gale Crater, Mars. (14th September 2017) - Edwards, Peter H.; Bridges, John C.; Wiens, Roger; Anderson, Ryan; Dyar, Darby; Fisk, Martin; Thompson, Lucy; Gasda, Patrick; Filiberto, Justin; Schwenzer, Susanne P.; Blaney, Diana; Hutchinson, Ian
Abstract: The ChemCam instrument on the Mars Science Laboratory (MSL) rover, Curiosity, observed numerous igneous float rocks and conglomerate clasts, reported previously. A new statistical analysis of single‐laser‐shot spectra of igneous targets observed by ChemCam shows a strong peak at 55 wt% SiO2 and 6 wt% total alkalis, with a minor secondary maximum at 47–51 wt% SiO2 and lower alkali content. The centers of these distributions, together with the rock textures, indicate that many of the ChemCam igneous targets are trachybasalts, Mg# = 27 but with a secondary concentration of basaltic material, with a focus of compositions around Mg# = 54. We suggest that all of these igneous rocks resulted from low‐pressure, olivine‐dominated fractionation of Adirondack (MER) class‐type basalt compositions. This magmatism has subalkaline, tholeiitic affinities. The similarity of the basalt endmember to much of the Gale sediment compositions in the first 1000 sols of the MSL mission suggests that this type of Fe‐rich, relatively low‐Mg#, olivine tholeiite is the dominant constituent of the Gale catchment that is the source material for the fine‐grained sediments in Gale. The similarity to many Gusev igneous compositions suggests that it is a major constituent of ancient Martian magmas, and distinct from the shergottite parental melts thought to be associated with Tharsis and the Northern Lowlands. The Gale Crater catchment sampled a mixture of this tholeiitic basalt along with alkaline igneous material, together giving some analogies to terrestrial intraplate magmatic provinces.